How to talk so little kids will listen : a survival guide to life with children ages 2-7 - Faber, Joanna; King, Julie (Parent educator) (Scribner, 2017)
With a combination of storytelling, cartoons, and fly-on-the-wall discussions from their workshops, Faber and King provide concrete tools and tips that will transform your relationship with the young kids in your life. What do you do with a little kid who ... won't brush her teeth ... screams in his car seat ... pinches the baby ... refuses to eat vegetables ... throws books in the library ... runs rampant in the supermarket? Organized according to common challenges and conflicts, this book is an emergency first-aid manual of communication strategies, including a chapter that addresses the special needs of children with sensory processing and autism spectrum disorders. This guide will empower parents and caregivers of young children to forge rewarding, joyful relationships with terrible two-year-olds, truculent three-year-olds, ferocious four-year-olds, foolhardy five-year-olds, self-centered six-year-olds, and the occasional semi-civilized seven-year-old. And, it will help little kids grow into self-reliant big kids who are cooperative and connected to their parents, teachers, siblings, and peers.